Silver Clusters of Five Atoms as Highly Selective Antitumoral Agents Through Irreversible Oxidation of Thiols. (15th March 2022) - Porto, Vanesa; Buceta, David; Domínguez, Blanca; Carneiro, Carmen; Borrajo, Erea; Fraile, María; Davila‐Ferreira, Nerea; Arias, Iria R.; Blanco, José M.; Blanco, Maria C.; Devida, Juan M.; Giovanetti, Lisandro J.; et al.
Abstract: Low atomicity clusters present properties dependent on the size, due to the quantum confinement, with well‐defined electronic structures and high stability. Here it is shown that Ag5 clusters catalyze the complete oxidation of sulfur to S +6 . Ag5 catalytic activity increases with different oxidant species in the order O2 ≪ H2 O2 < OH. Selective oxidation of thiols on the cysteine residues of glutathione and thioredoxin is the primary mechanism human cells have to maintain redox homeostasis. Contingent upon oxidant concentration, Ag5 catalyzes the irreversible oxidation of glutathione and thioredoxin, triggering apoptosis. Modification of the intracellular environment to a more oxidized state to mimic conditions within cancer cells through the expression of an activated oncogene (HRAS G12V ) or through ARID1A mutation, sensitizes cells to Ag5 mediated apoptosis. While cancers evolve to evade treatments designed to target pathways or genetic mutations that drive them, they cannot evade a treatment that takes advantage of aberrant redox homeostasis, which is essential for tumor progression and metastasis. Ag5 has antitumor activity in mice with orthotopic lung tumors reducing primary tumor size, and the burden of affected lymphatic nodes. The findings suggest the unique intracellular redox chemistry of Ag5 may lead to new redox‐based approaches to cancer therapy. Abstract : Ag5 clusters show unique catalytic activities to oxidize thiols. They catalyze the complete oxidation of thiols present in cysteine, glutathione, and thioredoxin. This oxidation is tunable by relevant biological oxidants species (hydrogen peroxide and hydroxyl radical), allowing Ag5 to inhibit the thiol‐based antioxidants leading to the selective death of tumor proliferating cells.